Distribution of findings of scorpions in Buenos Aires city in the period 2001-2012 and their sanitary implications - Blanco, Guillermo (2016)
Fil: Blanco, Guillermo. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Estudios de la Inmunidad Humoral "Prof. Ricardo A. Margni"; Argentina.